1997
DOI: 10.1093/emboj/16.20.6200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of CD95 (APO-1/Fas) signaling by ceramide mediates cancer therapy-induced apoptosis

Abstract: We report here that anticancer drugs such as doxorubicin lead to induction of the CD95 (APO‐1/Fas) system of apoptosis and the cellular stress pathway which includes JNK/SAPKs. Ceramide, which accumulates in response to different types of cellular stress such as chemo‐ and radiotherapy, strongly induced expression of CD95‐L, cleavage of caspases and apoptosis. Antisense CD95‐L as well as dominant‐negative FADD inhibited ceramide‐ and cellular stress‐induced apoptosis. Fibroblasts from type A Niemann–Pick patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
171
3
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(185 citation statements)
references
References 61 publications
10
171
3
1
Order By: Relevance
“…Stresses and cytokines may initiate signaling through the JNK cascade via receptor-associated adaptor molecules, SMase-mediated ceramide generation, or unknown mechanisms. JNK activation results in transcriptional upregulation of pro-apoptotic TNF superfamily members (Herr et al, 1997;Debatin, personal communication), but may also act directly to phosphorylate and inactivate Bcl-2 to promote apoptosis. Ceramide can also signal transcriptionally-independent apoptosis through mitochondria dysfunction, which, in one report, occurs by suppression of Akt kinase via a pathway regulated through Ras and Raf-1…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stresses and cytokines may initiate signaling through the JNK cascade via receptor-associated adaptor molecules, SMase-mediated ceramide generation, or unknown mechanisms. JNK activation results in transcriptional upregulation of pro-apoptotic TNF superfamily members (Herr et al, 1997;Debatin, personal communication), but may also act directly to phosphorylate and inactivate Bcl-2 to promote apoptosis. Ceramide can also signal transcriptionally-independent apoptosis through mitochondria dysfunction, which, in one report, occurs by suppression of Akt kinase via a pathway regulated through Ras and Raf-1…”
Section: Resultsmentioning
confidence: 99%
“…In some instances, ceramide generation and JNK activation may occur independently yet act coordinately to signal apoptosis. In this regard, Debatin and co-workers (Herr et al, 1997) showed that daunorubicin-induced ceramide generation was required for Fas-ligand upregulation and apoptosis as both events were inhibited in NPD cells. In contrast, daunorubicin-induced JNK stimulation was not attenuated in NPD cells although a requirement for JNK activation in induction of apoptosis was not evaluated in these studies.…”
Section: Targets For Jnk Signaling Of Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that chemotherapeutic drugs induce the expression of CD95 and CD95L. Therefore, it was proposed that drug-induced apoptosis is mediated in a paracrine or autocrine loop via CD95/CD95L interaction, analogously to T cell receptor-mediated cell death (Friesen et al, 1996;Fulda et al, 1997aFulda et al, , 1998MuÈ ller et al, 1997;Herr et al, 1998;Dhein et al, 1995). However, there are also reports indicating that anticancer drugs induce apoptosis independently of death receptors Wesselborg et al, 1999;Eischen et al, 1997;Gamen et al, 1997;Villunger et al, 1997;Fulda et al, 1997b;Tolomeo et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…31 Experiments were performed at least three times in triplicate and values given are the mean of triplicates7standard deviation. Surface stainings of TRAIL receptors were carried out as described, 24 except that biotinylated anti-mouse-IgG and streptavidin-APC were used according to the manufacturer's recommendations.…”
Section: Antibodies and Reagentsmentioning
confidence: 99%